2006
DOI: 10.1111/j.1744-7917.2006.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Conference summary

Abstract: Progress on the research and development of insect-resistant transgenic rice, especially expressing insecticidal proteins from Bacillus thuringiensis (Bt), in China has been rapid in recent years. A number of insect-resistant transgenic rice lines/varieties have passed restricted and enlarged field testing, and several have been approved for productive testing since 2002 in China, although none was approved for commercial use until 2006. Extensive laboratory and field trials have been conducted for evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Movement patterns and impacts on non-target organisms of Bt toxins through tritrophic interactions have been reported in some previous studies (reviewed by Romeis et al 2006 andChen et al 2006). However, the ecological impact of Bt toxin movement has not always been clearly evaluated.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Movement patterns and impacts on non-target organisms of Bt toxins through tritrophic interactions have been reported in some previous studies (reviewed by Romeis et al 2006 andChen et al 2006). However, the ecological impact of Bt toxin movement has not always been clearly evaluated.…”
Section: Discussionmentioning
confidence: 92%
“…Bt rice field trials were first conducted in China in 1998 and large field trials of several Bt rice lines have continued in China (Chen et al 2006;Wang and Johnston 2007). Field trials have confirmed that Bt rice effectively controls stem borers and leaffolders (Chen et al 2006). In a study in farmers' fields in China, a Bt rice line resulted in yield increases of 6-9%, and 80% reduction in insecticide use, in comparison to conventional varieties (Huang et al 2005).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the development of Bt rice lines, China made great efforts for independent innovation, and also took an active part in international cooperation. For example, KMD was developed by Zhejiang University in collaboration with the University of Ottawa, and Huahui 1 and Bt Shanyou 63 were developed by Huazhong Agricultural University in collaboration with the International Rice Research Institute [16]. Agrobacterium - and gene gun-mediated transformations are commonly used for Bt rice development, and the promoters used for driving the expression of Bt genes include ubiquitin , rice rbcS (small subunit of ribulose-1, 5-bisphosphate carboxylase/oxygenase) promoter, and Actin1 (Table 1).…”
Section: Bt Ricementioning
confidence: 99%